Chemical structure of organic matter of water-stable microaggregates of agrochernozems of different positions on the slope - Z. S. Artemyeva; Yu. G. Kolyagin; E. B. Varlamov; E. S. Zasukhina; E. V. Tsomaeva; N. V. Yaroslavtseva; B. M. Kogut (Бюллетень Почвенного института им. В.В. Докучаева)
The chemical structure of organic matter (OM) pools within water-stable free microaggregates, isolated from air-dry aggregates (2–1 mm) in arable horizons of non-eroded, eroded and deposited agrochernozems has been studied by solid-state 13C-NMR spectroscopy. An assessment is made of the alteration of their chemical structure in the denudative-accumulative landscape. It was revealed that the overwhelming majority of water-stable free microaggregates in erosion zone are the fragments of destroyed macroaggregates, mainly newly formed due to the dynamic replacement of OM in situ. This is clearly evidenced by the integral indicators of the chemical structure of all OM pools in free microaggregates of eroded agrochernozem compared to those of the non-eroded one: reduced OM decomposition index (DI), OM aromaticity index (ARI) and OM hydrophobicity index (HI). Analytical data indicate the predominant transport from the erosion zone of microaggregates, represented by fragments of destroyed and mainly newly formed macroaggregates. During the transport phase, the previously physically protected occluded OM of free microaggregates undergoes partial mineralization. Predominantly its most labile part (hydrolysable) is mineralized, and its stable part remains little/non-changed. Mineral-associated OM (Clay and Residue) changes little, maintaining relative freshness.